2017
DOI: 10.1111/1556-4029.13584
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences and Criminal Extremity: New Evidence for Sexual Homicide

Abstract: Adverse childhood experiences are associated with a wide range of behavioral, health, and psychiatric deficits and have recently been used to study the development of serious offending careers. Unfortunately, this research paradigm has largely ignored forensic populations. This study utilized the adverse childhood experiences framework to examine the associations between exposure to violence, victimization, and total adverse childhood experiences on sexual homicide using a sample of 616 incarcerated adult male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 44 publications
2
31
0
Order By: Relevance
“…The final aim of this study was to examine differences in the prevalence of ACEs among people with convictions for violent offences, sex offences and non-violent offences. Consistent with evidence that suggests higher ACE scores are associated with more serious offending patterns (DeLisi & Beauregard, 2018; Fox et al., 2015), the findings of this study lend further support to the role of ACEs in violent offending. Cumulative ACE scores were significantly higher among young people who had at least one conviction for a violent offence.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The final aim of this study was to examine differences in the prevalence of ACEs among people with convictions for violent offences, sex offences and non-violent offences. Consistent with evidence that suggests higher ACE scores are associated with more serious offending patterns (DeLisi & Beauregard, 2018; Fox et al., 2015), the findings of this study lend further support to the role of ACEs in violent offending. Cumulative ACE scores were significantly higher among young people who had at least one conviction for a violent offence.…”
Section: Discussionsupporting
confidence: 86%
“…have also demonstrated that a higher prevalence of ACEs among juvenile offenders is not only associated with increased risk of recidivism (Craig, Baglivio, Wolff, Piquero, & Epps, 2016; Wolff, Baglivio, & Piquero, 2017), but also with increased risk of suicide attempts (Perez, Jennings, Piquero, & Baglivio, 2016). Other research conducted in the United States has also demonstrated that a higher number of ACEs is associated with the perpetration of sexual homicide (DeLisi & Beauregard, 2018). This suggests that ACEs may be strongly associated with more serious criminal pathways, such as violent and chronic offending.…”
Section: Aces and Offending Behaviourmentioning
confidence: 97%
“…In another study, Beauregard and Delisi (2018;see also DeLisi & Beauregard, 2018) compared the same three groups of offenders but this time on several developmental factors.…”
Section: Sexual Homicide Versus Nonhomicidal Sexual Violencementioning
confidence: 99%
“…These are sobering data for multiple reasons. There is a huge amount of evidence that sexual victimization is associated with subsequent internalizing disorders (Aday, Dye, & Kaiser, 2014;Kennedy & Prock, 2018;Turner, Finkelhor, & Ormrod, 2010), externalizing disorders (Miley, Fox, Muniz, Perkins, & DeLisi, 2020;Renner, Boel-Studt, & Whitney, 2018), impaired socioeconomic and social functioning (Hochstetler, DeLisi, Jones-Johnson, & Johnson, 2014;Kennedy & Prock, 2018), increased overall psychopathology (Najdowski & Ullman, 2009;Romano & De Luca, 2001), suicidal thoughts and behaviors (Aday et al, 2014), and, among males, becoming a sexual offender -567 (DeLisi & Beauregard, 2018;Drury, Elbert, & DeLisi, 2019;DeLisi, Kosloski, Vaughn, Caudill, & Trulson, 2014;Miley et al, 2020). Thus these victimizations are devastating to the victim and set into motion multiple, interrelated, immediate and long-term negative consequences.…”
Section: Discussionmentioning
confidence: 99%